2015
DOI: 10.1002/2015jd023304
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory modeling of modern dust transport to the Southern Ocean and Antarctica

Abstract: Aerosol deposition over the Southern Ocean and Antarctica has the potential to alter marine productivity and thus ocean carbon uptake while also impacting radiative balance due to scattering and absorption from atmospheric particulates. Quantification of modern emission, transport, and deposition of terrestrial dust and other airborne material from Southern Hemisphere sources is challenging due to low emission levels and poor detection from remote sensing platforms. Here forward trajectory modeling is used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
127
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(139 citation statements)
references
References 93 publications
12
127
0
Order By: Relevance
“…Victoria Lower Glacier, to the east of RICE) show a clear cooling trend prior to 1900 CE, and together this points to a more complex picture of the evolution of the atmospheric circulation around the Ross Sea than can be captured with the current network of cores. The RICE δ 18 O record, situated on Roosevelt Island on the Ross Ice Shelf, is more influenced by air masses from the eastern Ross Sea sector than the rest of the West Antarctic Ice Sheet region, which is influenced predominantly by air masses from the Amundsen Sea (Neff et al, 2015;. Moreover, borehole temperature and δ 15 N thermal fractionation records at RICE highlight some notable differences in the isotope temperature reconstruction, which suggest that sea ice extent exerts an important control, perhaps masking aspects of the longer-term temperature trends in the region .…”
Section: Long-term Trends In Weighted Reconstructionsmentioning
confidence: 99%
“…Victoria Lower Glacier, to the east of RICE) show a clear cooling trend prior to 1900 CE, and together this points to a more complex picture of the evolution of the atmospheric circulation around the Ross Sea than can be captured with the current network of cores. The RICE δ 18 O record, situated on Roosevelt Island on the Ross Ice Shelf, is more influenced by air masses from the eastern Ross Sea sector than the rest of the West Antarctic Ice Sheet region, which is influenced predominantly by air masses from the Amundsen Sea (Neff et al, 2015;. Moreover, borehole temperature and δ 15 N thermal fractionation records at RICE highlight some notable differences in the isotope temperature reconstruction, which suggest that sea ice extent exerts an important control, perhaps masking aspects of the longer-term temperature trends in the region .…”
Section: Long-term Trends In Weighted Reconstructionsmentioning
confidence: 99%
“…[] suggest that dust originating at latitudes >60°N accounts for 27% of the total atmospheric dust load in the Arctic, with 38% being transported to the region from Asia and a farther 32% from Africa. Using air parcel trajectory modeling of atmospheric transport pathways, Neff and Bertler [] concluded that the high‐latitude dust sources in New Zealand and Patagonia were more likely to contribute dust to the Southern Ocean and Antarctica than sources in subtropical southern Africa or Australia. An important result of Neff and Bertler 's [] study concerns the potential vertical profile of dust in the atmosphere.…”
Section: Regional and Global Dust Emissions From High Latitudesmentioning
confidence: 99%
“…During atmospheric transport, the dust could be deposited via dry and wet deposition (Mahowald et al, ); however, the actual deposition processes are not explored in this study. Other studies have shown that the accuracy of HYSPLIT trajectories based on reanalysis data is robust and highly correlated with station measurements in the Southern Hemisphere (Neff & Bertler, ). HYSPLIT provides an opportunity to simulate the long‐range transport of dust emitted by continental sources that are included in this study.…”
Section: Methodsmentioning
confidence: 93%